Time of urine sampling may influence the association between urine specific gravity and body composition - Patrick B. Wilson; Brian K. Ferguson; Ian P. Winter (PLoS ONE, 2025)
Urine specific gravity (USG) is frequently utilized in sports practice and research to assess hydration status. Prior research suggests that individuals with large amounts of fat-free mass (FFM) and muscle have elevated USG, but little is known about whether the time of collection (first-morning vs. spot sampling) and various nutritional factors influence these relationships. This cross-sectional, observational study assessed fasted first-morning (n = 55) and non-fasted spot USG (n = 51) samples in adults and evaluated relationships of USG with body composition and nutrition intake. The InBody 770 was used to estimate FFM, skeletal muscle mass (SMM), and total body water (TBW). Protein, water, and sodium intakes from the 24-hour period before USG assessments were generated based on the Automated Self-Administered 24-hour Recall. Median USG was higher for fasted first-morning samples than non-fasted spot samples (1.018 vs. 1.011, Z = −5.2, p < 0.001). Based on fasted first-morning samples, 41.8% of participants had a USG ≥ 1.020 while the prevalence of USG ≥ 1.020 was 21.6% using non-fasted spot samples. None of the body composition variables (FFM, SMM, TBW) significantly associated with fasted first-morning USG (Spearman ρ < 0.10), while all three variables showed significant, positive associations with non-fasted spot USG (Spearman ρ = 0.32–0.36, p < 0.05). None of the dietary variables were significantly associated with either fasted first-morning or non-fasted spot USG. Although previous research has shown the FFM positively associates with USG, this investigation provides evidence that this relationship could depend on sampling time. Non-fasted spot samples, in comparison to fasted first-morning samples, may be impacted by FFM to a greater degree.